Ireland, the Great War, and the geography of remembrance - Johnson, Nuala Christina, 1962- (Cambridge studies in historical geography ;, 2003)
The Irish experience of the Great War, and its commemoration, is the location of Nuala C. Johnson's sustained and pioneering examination of the development of memorial landscapes, and her study represents a major contribution both to cultural geography and to the historiography of remembrance.